Relationship Between Neutrophil-to-Lymphocyte Ratio and High-Density Lipoprotein with Major Cardiovascular Events in Acute Myocardial Infarction with ST-Segment Elevation Undergoing Primary Percutaneous Coronary Intervention at Adam Malik Hospital, Medan - Adam, Faisal; Hasan, Harris; Haykal, T. Bob (CoinReads Media Prima, 2025)
Introduction: Coronary artery calcium score (CACS) is a specific indicator of coronary atherosclerosis that plays a role in assessing the degree of calcification in atherosclerosis. Diastolic function is the first aspect of cardiac function to be impaired in ischemic heart disease. This study aims to determine the relationship between calcium scoring and diastolic dysfunction. Methods: This analytical observational study with cross-sectional design evaluated the relationship between coronary artery calcium score (CACS) and left ventricular diastolic function in patients with stable CAD. Data were collected retrospectively from medical records at RSUP H. Adam Malik Medan during Nov 2023-Nov 2024. CACS was assessed using coronary CT scan, while left ventricular diastolic function was measured by echocardiography. Data analysis used chi-square test, Mann-Whitney U test, and ROC curve analysis to evaluate CACS threshold in predicting diastolic dysfunction. Results: Among 158 analyzed samples, 113 patients had diastolic dysfunction. A calcium score ≥100 was found in 46.2% of patients, showing 1.318 times higher risk of diastolic dysfunction versus those with scores <100 (p = 0.006; 95% CI 1.083–1.605). ROC analysis showed CACS had moderate predictive ability for diastolic dysfunction with AUC of 0.647 (p = 0.004). A calcium score threshold of 45 had 65.5% sensitivity and 62.2% specificity in detecting diastolic dysfunction. Type 2 diabetes mellitus, urea, and creatinine levels were also significantly associated with diastolic dysfunction (p < 0.05). Conclusion: Calcium score shows a significant relationship with diastolic dysfunction in stable CAD patients and can predict diastolic dysfunction in patients undergoing coronary CT scan.